Characterization and Identification of Indol Acetic Acid Phytohormone-producing Bacteria from Corn Root (Zea mays L.) - Putri Maharani, Rendha; Aeni Ariyanti, Nur; Aloysius, Suyitno; Sugiyarto, Lili (Jurnal Sains Dasar, 2025)
Rhizobacteria are endophytic bacteria that inhabit plant tissues and the rhizosphere, producing secondary metabolites that support plant growth. This study is an exploratory descriptive investigation aimed at characterizing and identifying IAA- and phytohormone-producing endophytic rhizobacteria isolated from the roots of corn plants (Zea mays L.). The rhizobacteria isolates producing IAA phytohormones were obtained by culturing bacteria in Yeast Peptone Broth (YPB) medium supplemented with L-tryptophan. Bacterial cultures (1 mL) were treated with Salkowski reagent, and absorbance was measured spectrophotometrically at a wavelength of 530 nm. From 14 isolates, five were identified as producing the highest levels of indole-3-acetic acid (IAA), ranging from 17 to 50 ppm. Identification was conducted using the profile matching method to determine the genus of each rhizobacterium by comparing its characteristics with reference genera. Based on 62 tested traits, the five isolates exhibited diverse features, including Gram-positive and Gram-negative bacteria, coccus-shaped morphology, circular and irregular colony configurations, lobate and undulate margins, convex, umbonate, and raised elevations, and colony colors ranging from white to yellowish, along with varied physiological (biochemical) test results. The identification results revealed bacteria with a similarity index of ≥70%, suggesting proximity to the genus Micrococcus (77.4%, isolate N), Rhizobium (80.6%, isolate D), and Shewanella (80.6%, isolate B; 87.1%, isolate V; and 91.9%, isolate E). This research provides an important contribution to the development of biofertilizers aimed at enhancing the growth and productivity of corn plants sustainably.